Creation of fully degradable poly(lactic acid) composite by using biosourced poly(4-hydroxybutyrate) as bioderived toughening additives - Tianshu Zhang; Hao Wu; Huaping Wang; Abin Sun; Ze Kan (eXPRESS Polymer Letters)
The inherent brittleness of poly(lactic acid) (PLA) limited its practical applications, so toughening modification was necessary. Poly(4-hydroxybutyrate) (P4HB) is fully biosourced and biodegradable polyester with the advantages of high strength and good toughness. In this study, P4HB was used to toughen PLA. The effects of composition, molecular weight, and processing method on the toughening of PLA were investigated. Tensile testing showed the elongation at failure of the PLA/P4HB composites increased with the increased P4HB content while the ultimate tensile strength gradually decreased. The composite containing 30% P4HB can offer a 40 times increase in elongation at failure compared with neat PLA. In the meantime, the ultimate tensile strength remained 48 MPa. Furthermore, the particle size and distribution of P4HB in PLA were tailored by changing the molecular weight and processing method to obtain a higher impact toughness. Importantly, there was a peak in impact strength (27 kJ/m2) of the PLA/P4HB composites when the particle size of P4HB was in the range of 1.1–1.3 μm. This study provides not only a new toughener to prepare fully degradable PLA with high toughness and high strength but also sets up a universal framework for designing high-performance PLA products with suitable toughener particle sizes.